Differences in central dopamine, but not serotonin, activity and welfare associated with age but not with preening cup use in commercial grow-out Pekin duck barns - M.M. Bergman; J.M. Schober; R. Novak; A. Grief; C. Plue; D. Frey; H. Parnin; G.S. Fraley (Poultry Science)
Preening cups are a semi-open water source for Pekin duck enrichment. To evaluate the ducks’ affective state, we combined measuring welfare by walking a transect in the barn with mass spectrometry and qRT-PCR to measure brain neurotransmitter levels and gene expression for serotonin (5-HT) and dopamine (DA) synthesis and metabolism. 5-HT and DA have been established as indicators of mental state and emotions. We visited 4 standard commercial barns that housed approximately 6000–9000 ducks (one preening cup per 1500 ducks) and collected samples on d21 prior to preening cup placement, d28 one week after preening cup placement, and d35 one day prior to processing. Litter samples (n = 3/barn/day) were collected and transect walks were conducted to evaluate the welfare of the birds. Brain samples (n = 8/day/barn) were collected from two locations: ducks actively using the preening cups (PC) and ducks across the barn not actively using the preening cups (CON). The brains were hemisected and dissected in three brain areas: caudal mesencephalon (CM), rostral mesencephalon (RM), and diencephalon (DI). Litter samples showed no significant differences between collection dates. The transect showed significant differences in feather quality, feather cleanliness, and eye due to age, but not preening cups. The right hemisphere showed no differences in 5-HT turnover. For DA turnover, there are differences in CM (p < 0.05) and DI (p < 0.001) over time, but no differences between PC and CON. The left hemisphere measured TPH1, TPH2, and TH. CM and DI brain areas are not significantly different. Within the RM, there is a significant increase in TPH1 expression for ducks on d35 when compared to ducks on d28 and d21. These results suggest that 5-HT and DA do not differ due to duck location. However, DA activity increases as these ducks age. DA is an important neurotransmitter and activity increases as an animal grows allowing for behavioral development. Our data shows that commercial preening cups do not negatively impact ducks’ welfare or affective state.